Post-stroke depression: predictors and prophylaxis - Muratova, T. M.; Khramtsov, D. M.; Stoyanov, O. M.; Vorokhta, Yu. M.; Vikarenko, M. S.; Kozlova, G. G. (Journal of Education, Health and Sport, 2019)
The purpose of the study was to evaluate the effectiveness of prevention of post-stroke depression in patients with acute cerebrovascular accidentIt was shown that the incidence of PID in patients with ischemic stroke exceeds 30%. In assessing the role of various risk factors among the examined patients with PID, the prevalence of male patients (OR = 1.3 (1.1-1.5)), under the age of 55 (1.7 (1.3-1.9 )), with indications in the history of episodes of depression in the past (1.6 (1.4-1.8)), as well as alcohol abuse (1.2 (1.0-1.3)). In 31 (58.5%) there was a localization of focal ischemia in the frontal lobe of the dominant hemisphere. The use of both SIRS and an antidepressant with multimodal effect - vortioxetine was sufficiently effective in PID, but vortioxetin showing the best results - from 8,80,1 points to 6,20,1 points. The paper considers the expediency of the use of vorothoxetine in order to prevent PID in patients with ischemic stroke.